2005
DOI: 10.1051/lait:2005041
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis and sensory characteristics of Cheddar cheeses ripened using different temperature-time treatments

Abstract: -Commercial Cheddar cheeses were ripened under each of 7 temperature-time treatments ranging in temperature from 4 to 12°C for a total of 270 d. The levels of total and individual free fatty acids (FFA), as measured by gas chromatography, increased with increasing ripening temperature and progressive ripening time for all 7 cheeses. Increasing ripening temperature by 4°C, from 8 to 12°C, resulted in a greater relative increase in the accumulation of FFA than a ripening temperature increase of the same magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…The storage of Ras cheese at this temperature accelerates lipolysis. Similar results were obtained by Mahony et al [34] who studied the effect of temperature from 4˚C to 12˚C for ripened of commercial Cheddar cheeses for a total of 270 days. They found that, the levels of total and individual free fatty acids increased with increasing ripening temperature and progressive ripening time.…”
Section: Efficiency Of the Fungal Strains For Lipolysissupporting
confidence: 87%
“…The storage of Ras cheese at this temperature accelerates lipolysis. Similar results were obtained by Mahony et al [34] who studied the effect of temperature from 4˚C to 12˚C for ripened of commercial Cheddar cheeses for a total of 270 days. They found that, the levels of total and individual free fatty acids increased with increasing ripening temperature and progressive ripening time.…”
Section: Efficiency Of the Fungal Strains For Lipolysissupporting
confidence: 87%
“…As claimed in previous works (Aston, Fedrick, Durward, & Dulley, 1983;Ferrazza, Fresno, Ribeiro, Tornadijo, & Mansur Furtado, 2004;Hannon et al, 2005;O'Mahony et al, 2006), application of high Food Research International 48 (2012) 34-40 storage temperatures during the initial stages of ripening appears to cause a moderate and equilibrated increase in the activity of enzymatic systems, whereas a reduction in the risk of microbiologic contamination or unbalance in biochemical reactions could be achieved. Consequently, application of higher initial storage temperatures emerges as an interesting alternative instead of treatments based on ripening at high temperatures during the whole ripening period.…”
Section: Introductionmentioning
confidence: 67%
“…Increasing storage temperature is the simplest method available for the acceleration of cheese ripening period, and it has the additional benefit of potential savings resulting from lower refrigeration costs (O'Mahony, Sheehan, Delahunty, & McSweeney, 2006). Main drawbacks mentioned for this technology are an increased risk of development of undesirable microorganisms and non-specific increases in ripening reactions that can lead to the presence of unbalanced flavours or off-flavours, together with potential body defects such as softening or crumbliness (Law, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing storage temperature stands out as being a simple and inexpensive alternative that can represent additional benefits resulting from lower refrigeration costs (O'Mahony et al . ). Another advantage associated with this technology is that no external agents are added to the cheese mass so overcoming potential restrictions set by product regulations, as Protected Denomination of Origin (P.D.O.…”
Section: Introductionmentioning
confidence: 97%